PENGARUH PENGAWASAN KOMITE AUDIT, AUDIT INTERNAL, AUDIT EKSTERNAL TERHADAP KESEHATAN KEUANGAN PERUSAHAAN DAN DAMPAKNYA TERHADAP PROFITABILITAS - Merawati, Endang Etty; Hatta, Iha Haryani (Jurnal Akuntansi, 2014)
Insurance and reinsurance companies are required, to maintain a soundfinancial standing and comply with the provisions on the companies equity as stipulated by the government. To achieve such equity, the companies must retain their profitability. Under a supervision system supported by the audit committee, internal auditor and external auditor, it is expected that the insurance companies shall be able to fulfill their obligation in complying with all the prevailing regulations. If these companies fail to do so, the companies shall be subject to the supervision by the government. This study was conducted on insurance and reinsurance companies listed in the Indonesian Stock Exchange in 2012 (11 companies). Thirty eight high officials of the top management of the companies were interviewed as respondents. By applying the SPSS program the results showed that there are significant relations among the audit committee, the internal and external auditor in supervising the operations of the insurance companies. There is a positive correlation between the audit committee and the internal auditor; and there is a positive correlation between the audit committee and the external auditor whereas there is also a positive correlation between the internal auditor and the external auditor. Simultaneous influence of the audit committee, the internal audit and the external audit shows a positive effect on the financial soundness. However, external audit has only partial influence on the financial soundness. The simultaneous influence of audit committee, audit internal, audit external and financial soundness shows a significant effect on the profitability. The partial influence on each independent variabel (mentioned above) has a significant effect on the profitability.